Zróżnicowanie polityki inwestycyjnej otwartych funduszy emerytalnych - Trippner, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The case study concerns obligatory tasks that have to be fulfilled by open pension funds within the scope of conducted investment policy. The legislative body possesses administrative tools for evaluation and control investment fund policies. The author analyzes the influenced of these tools on the independence of investment policy. As a result, an answer to the question whether current regulations promote an independence of open pensions funds investment policy is given. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 457-464